Poul Martin Møller: Poet, Philosopher and Philologist - Bravo, Nassim; Jensen, Finn Gredal; Stewart, Jon (Danish Golden Age Studies, 2026)
Poul Martin Møller (1794-1838) was a well-known figure in Golden Age Denmark, and his versatile intelligence was acknowledged by his contemporaries. Møller was a philologist, novelist, poet, theologian and philosopher, and his work included poems, translations, philosophical essays, aphorisms, reviews, and the fragment of a novel. His sudden death in 1838 interrupted what could have been a brilliant intellectual career. This anthology offers a series of articles written by leading scholars specialized in the Danish Golden Age; the aim is to shed light on different aspects of Møller's thought and to show how his ideas may still be relevant to us.